Introductory econometrics - Dhrymes, Phoebus J. (New York : Springer-Verlag, 1978)
The selection of topics and the level of discourse give sufficient variety so that the book can serve as the basis for several types of courses.
Includes index.
Bibliography: p. 553-554.
rpm 13/09/2017
Loans
Keywords: Econometrics